Impact of working capital management on growth of Malaysia companies: An empirical investigation of public listed companies - Syed Fairul Afis, Syed Mustapha (2015)
Working capital management has always drawn the attention of the corporate sectors. Public listed companies particularly place strong emphasis on an effective and efficient working capital management for their survival and growth. Its contribution is not only on profitability, but also in determining the liquidity of assets to offset current obligations. This study analyses and measures the relationship between working capital management and growth of public listed companies in Malaysia. Specifically, the study examines the relationships between the four components of working capital management, namely, cash conversion cycle, receivable conversion period, inventory conversion period, payable conversion period and the growth of Malaysian publicly listed companies. The study utilizes the financial historical data obtained from the DataStream from December 2009 to December 2013. The one hundred top public-listed companies main (based on market capitalization) in the Main Board of Bursa Malaysia are selected as a sample. The testing for hypotheses involved examining the relationship between the dependent variable (growth of Malaysia companies) and the independent variables (cash conversion cycle, receivable conversion period, inventory conversion period, and payable conversion period). Analysis shows that all the independent variables have positive relationships with firm growth, but only cash conversion cycle has a significant relationship. It is concluded that companies should focus and establish the policy of working capital management in an efficient manner to serve their shareholders in maximizing their wealth.